The spread of Bombus haematurus in Italy and its first DNA barcode reference sequence - Biella, Paolo; Galimberti, Andrea (Fragmenta entomologica, 2020)
Climate change and human activities are impacting species distribution, and thus, tracking species movements is a key aspect for their conservation and for understanding their biology. Among the bumblebees that are changing distribution, one of the most striking cases of a fast and natural range expansion is the eastern Mediterranean Bombus haematurus. Here we report the first Italian records of this species, with observations from the N-E Italy at a distance of 332 Km from the edge of the historical distribution. These are the westernmost known occurrences of this species and they are not far from a large series of records in several Central European countries of recent colonization. Here, we also obtained and made publicly available the reference COI barcode sequence of Bombus haematurus and shown that is significantly different from other similar species at this genetic marker. Coupling morphology, field-data and genetic identity should greatly improve the efficiency of tracking species movements and therefore also their knowledge in both recently colonized and historical areas.